Evaluation of Voiding Dysfunction in Patients with Traumatic Brain Injury - Kumar, Amit; Vaddi, Suryaprakash; Gouru, Vijayabhaskar Reddy; Agrawal, Amit (Indian Journal of Neurotrauma, 2018)
Introduction Voiding dysfunction after a traumatic brain injury (TBI) occurs secondary to impaired cognitive or behavioral functioning, brain damage, associated injury to the spinal cord, and direct bladder trauma. In this study, the authors collected data on TBI patients with neurogenic bladder dysfunctions to understand the spectrum of voiding dysfunctions and to investigate the relationships of the severity of TBI with the presentation of urinary tract dysfunctions.Materials and Methods All consecutive patients with isolated TBI of Glasgow Coma Scale (GCS) (9–15) in the postacute period and at 3 months were included in the study. In patients with previous stroke or any other neurologic disorder or associated spine injury and with urologic conditions such as benign prostatic hyperplasia (BPH), the urethral stricture is excluded. After a successful voiding trial, uroflowmetry to see the flow pattern and ultrasound of the abdomen and pelvis for post-void residual urine is done. A urodynamic study is done in patients with poor urinary flow (< 15 mL/s), high post-void residual urine (> 100 mL), and/or lower urinary tract symptoms.Results During the study period, a total of 55 patients were enrolled in the study: 43 were males and 12 were females. Out of 55 patients, 47 were treated conservatively and 8 were operated upon for TBI. Out of 55 patients, 26 had a poor stream on uroflowmetry and 19 underwent urodynamic study either due to urinary symptoms or poor stream. Out of the 19 patients, 9 had a urodynamic abnormality. Of the 19 patients who underwent urodynamic study, there was no significant correlation (p = 0.23) between the TBI pathology and urodynamic abnormality. There was also no significant correlation seen between site of lesion and urodynamic abnormality.Conclusion The prevalence of urinary symptoms in mild and moderate TBIs is low (7.3); 47.7% of patients had poor urinary flow. None of the patients had an abnormality in filling phase. Nine patients had an abnormality in voiding phase and were treated with an α-blocker.Duration During 2012 to 2015.
Keywords: traumatic brain injury; voiding dysfunction; urinary bladder